(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
The article clarifies the specifics of the realization of the modes of being in the novel «Garden of Gethsemane» by Ivan Bagryany. To reveal the sources of the formation of ideological priorities of I. Bagryany and the specific features of his artistic philosophy, their comparison with the most characteristic phenomena of the European philosophical and aesthetic thought of the mid-twentieth century was carried out. Links with the philosophy of existentialism are found, due to the dramatic-intense experience of his hero of his being-existence, manifested through the phenomenon of unconditional inner freedom, as opposed to the sharply limited external.